The evaluation of sleep disturbances for Chinese frontline medical workers under the outbreak of COVID-19 - Qi, Jing; Xu, Jing; Li, Bo-Zhi; Huang, Jin-Sha; Yang, Yuan; Zhang, Zhen-Tao; Yao, Dong-Ai; Liu, Qun-Hui; Jia, Min; Gong, Dao-Kai; Ni, Xiao-Hong; Zhang, Qi-Mei; et al. (Sleep medicine, 2020)
To evaluate sleep disturbances of Chinese frontline medical workers (FMW) under the outbreak of coronavirus disease 2019 (COVID-19), and make a comparison with non-FMW. The medical workers from multiple hospitals in Hubei Province, China, volunteered to participate in this cross-sectional study. An online questionnaire, including Pittsburgh Sleep Quality Index (PSQI), Athens Insomnia Scale (AIS) and Visual Analogue Scale (VAS), was used to evaluate sleep disturbances and mental status. Sleep disturbances were defined as PSQI>6 points or/and AIS>6 points. We compared the scores of PSQI, AIS, anxiety and depression VAS, as well as prevalence of sleep disturbances between FMW and non-FMW. A total of 1306 subjects (801 FMW and 505 non-FMW) were enrolled. Compared to non-FMW, FMW had significantly higher scores of PSQI (9.3 ± 3.8 vs 7.5 ± 3.7; P < 0.001; Cohen's d = 0.47), AIS (6.9 ± 4.3 vs 5.3 ± 3.8; P < 0.001; Cohen's d = 0.38), anxiety (4.9 ± 2.7 vs 4.3 ± 2.6; P < 0.001; Cohen's d = 0.22) and depression (4.1 ± 2.5 vs 3.6 ± 2.4; P = 0.001; Cohen's d = 0.21), as well as higher prevalence of sleep disturbances according to PSQI > 6 points (78.4% vs 61.0%; relative risk [RR] = 1.29; P < 0.001) and AIS > 6 points (51.7% vs 35.6%; RR = 1.45; P < 0.001). FMW have higher prevalence of sleep disturbances and worse sleep quality than non-FMW. Further interventions should be administrated for FMW, aiming to maintain their healthy condition and guarantee their professional performance in the battle against COVID-19. •Frontline COVID-19 medical workers have a high prevalence of sleep disturbances.•Females have worse sleep quality than males among frontline medical workers.•Further interventions are needed to improve sleep disorders of medical workers.